2022
DOI: 10.4028/p-64226e
|View full text |Cite
|
Sign up to set email alerts
|

Self-Sensing Hybrid Fibre-Reinforced Polymer for Structural Health Monitoring (SHM)

Abstract: Hybrid composite material has been widely used in many engineering applications (e.g., for automobiles)and has several advantages over conventional fibre-reinforced composite materials, such as high strength-to-weight ratio and low cost. However, combining two kinds of reinforcement fibre within a common matrix may lead to different failure modes, such as delamination between the layers and fragmentation when the structure is subjected to high loads. To avoid this problem, real-time damage detection should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The onset of deterioration or failure occurred at the turning point where the capacitive value began to decrease. It has been shown that the embedded sensor into the Kevlar-carbon composite had a linear response over a broad range of axial stress (up to 170 MPa) compared to it embedded into a glass-carbon hybrid composite which is up to 100 MPa [3]. The observed improvement may be attributed to a significant difference of the Young's modulus between glass and carbon fibers which was minimized by hybridization of Kevlar fibers with carbon fibers, in turn leading to delaying the onset of failure at the turning point.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of deterioration or failure occurred at the turning point where the capacitive value began to decrease. It has been shown that the embedded sensor into the Kevlar-carbon composite had a linear response over a broad range of axial stress (up to 170 MPa) compared to it embedded into a glass-carbon hybrid composite which is up to 100 MPa [3]. The observed improvement may be attributed to a significant difference of the Young's modulus between glass and carbon fibers which was minimized by hybridization of Kevlar fibers with carbon fibers, in turn leading to delaying the onset of failure at the turning point.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings indicated that damage occurred at an early stage of axial stress. In a study by Alblalaihid et al [ 29 , 30 ], a smart intra-ply hybrid composite material (comprising glass fiber and carbon fiber) based on capacitance was developed. It was observed that failure occurred at a low level of axial stress due to the combination of low-elongation and high-elongation fibers within a common matrix.…”
Section: Introductionmentioning
confidence: 99%